1999
DOI: 10.1029/1998jc900010
|View full text |Cite
|
Sign up to set email alerts
|

The connectivity of eddy variability in the Caribbean Sea, the Gulf of Mexico, and the Atlantic Ocean

Abstract: Table 1) with 1/2 ø resolution is utilized. After spin-up to statistical equilibrium, all of the simulations were forced by daily averaged winds from 1981 to 1994, so that interannual variability is also present. The formulation for the NLOM is presented in section 2 with detailed equations for the thermodynamic version. The modifications necessary to create a hydrodynamic version are also presented as well as a more detailed discussion of the design of the three simulations specifically used in this study.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
86
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 36 publications
15
86
1
2
Order By: Relevance
“…All available in situ and most remote observations indicate that most NBC rings turn northward upon reaching the shoaling topography east of the Lesser Antilles and pass very near the island of Barbados. While some numerical simulations and satellite altimeter observations suggest that some NBC rings somehow pass intact through the narrow passages of the Lesser Antilles (e.g., Murphy et al 1999;Carton and Chao 1999;Goni and Johns 2003), available in situ observations indicate that the rings themselves are destroyed east of the island arc and only filaments of ring core fluid (e.g., as identified by Lagrangian drifters) are able to enter the eastern Caribbean. We find that NBC rings rarely encounter the Lesser Antilles in a frontal collision.…”
Section: Discussionmentioning
confidence: 99%
“…All available in situ and most remote observations indicate that most NBC rings turn northward upon reaching the shoaling topography east of the Lesser Antilles and pass very near the island of Barbados. While some numerical simulations and satellite altimeter observations suggest that some NBC rings somehow pass intact through the narrow passages of the Lesser Antilles (e.g., Murphy et al 1999;Carton and Chao 1999;Goni and Johns 2003), available in situ observations indicate that the rings themselves are destroyed east of the island arc and only filaments of ring core fluid (e.g., as identified by Lagrangian drifters) are able to enter the eastern Caribbean. We find that NBC rings rarely encounter the Lesser Antilles in a frontal collision.…”
Section: Discussionmentioning
confidence: 99%
“…However, some numerical simulations (Murphy et al, 1999;Carton and Chao, 1999;Barnier et al, 2001;Garraffo et al, 2003) and previously cited satellite altimeter observations suggest that some NBC rings do somehow pass intact through the narrow passages of the LA. In particular, the results described in Garraffo et al (2003), based on a high-resolution (6 km) Miami isopycnal coordinate model, indicate that as the rings approach the Lesser Antilles, some of them appear to enter the Caribbean nearly intact.…”
Section: Introductionmentioning
confidence: 99%
“…These mesoscale eddies and meanders with sizes of 100-500 km travel along the Caribbean Current axis [Fu and Holt, 1983]. Moreover, in the northeastern Caribbean, fluctuations have been noted to be stronger than the mean currents [Molinari et al, 1981] Simulations using the U.S. Navy Layered Ocean Model [Wallcraft, 1991] (a 1/4 ø resolution model with a 5.5-layer reduced gravity and a six-layer model with realistic bottom topography, having an explicit numerical scheme for the reduced gravity, formulated using an Arakawa "C" grid) by Murphy et al [1999] indicated eddy motion penetrated the Lesser Antilles and propagated across the Caribbean in -2 months. Similar eddies can form by horizontal shear instability in two-layer and reduced gravity models [Heburn et al, 1982] and can also be produced when eddies from the North Atlantic Ocean impinge on the Lesser Antilles as in the model of Capella [ 1994].…”
mentioning
confidence: 99%